TMV Particles: The Journey From Fundamental Studies to Bionanotechnology Applications - Lomonossoff, George P; Wege, Christina (Advances in virus research, 2018)
Ever since its initial characterization in the 19th century, tobacco mosaic virus (TMV) has played a prominent role in the development of modern virology and molecular biology. In particular, research on the three-dimensional structure of the virus particles and the mechanism by which these assemble from their constituent protein and RNA components has made TMV a paradigm for our current view of the morphogenesis of self-assembling structures, including viral particles. More recently, this knowledge has been applied to the development of novel reagents and structures for applications in biomedicine and bionanotechnology. In this article, we review how fundamental science has led to TMV being at the vanguard of these new technologies.